2016
DOI: 10.1371/journal.pone.0161193
|View full text |Cite
|
Sign up to set email alerts
|

Self-Amplifying mRNA Vaccines Expressing Multiple Conserved Influenza Antigens Confer Protection against Homologous and Heterosubtypic Viral Challenge

Abstract: Current hemagglutinin (HA)-based seasonal influenza vaccines induce vaccine strain-specific neutralizing antibodies that usually fail to provide protection against mismatched circulating viruses. Inclusion in the vaccine of highly conserved internal proteins such as the nucleoprotein (NP) and the matrix protein 1 (M1) was shown previously to increase vaccine efficacy by eliciting cross-reactive T-cells. However, appropriate delivery systems are required for efficient priming of T-cell responses. In this study,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
91
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 109 publications
(95 citation statements)
references
References 67 publications
3
91
0
1
Order By: Relevance
“…As little as 100 ng of an RNA replicon vaccine encoding RSV F, complexed to LNP, resulted in potent T and B cell immune responses in mice, and 1 μg elicited protective immune responses against RSV infection in a cotton rat intranasal challenge system 19 . SAM vaccines encoding influenza virus antigens in LNPs or an oil-in-water cationic nanoemulsion induced potent immune responses in ferrets and conferred protection from homologous and heterologous viral challenge in mice 9496 . Further studies demonstrated the immunogenicity of this vaccine platform against diverse viruses in multiple species, including human cytomegalovirus (CMV), hepatitis C virus and rabies virus in mice, HIV-1 in rabbits, and HIV-1 and human CMV in rhesus macaques 50,87,97 .…”
Section: Mrna Vaccines Against Infectious Diseasesmentioning
confidence: 99%
“…As little as 100 ng of an RNA replicon vaccine encoding RSV F, complexed to LNP, resulted in potent T and B cell immune responses in mice, and 1 μg elicited protective immune responses against RSV infection in a cotton rat intranasal challenge system 19 . SAM vaccines encoding influenza virus antigens in LNPs or an oil-in-water cationic nanoemulsion induced potent immune responses in ferrets and conferred protection from homologous and heterologous viral challenge in mice 9496 . Further studies demonstrated the immunogenicity of this vaccine platform against diverse viruses in multiple species, including human cytomegalovirus (CMV), hepatitis C virus and rabies virus in mice, HIV-1 in rabbits, and HIV-1 and human CMV in rhesus macaques 50,87,97 .…”
Section: Mrna Vaccines Against Infectious Diseasesmentioning
confidence: 99%
“…Vaccination with self-amplifying mRNA (SAM®) (GlaxoSmithKline, London, UK) in lipid nanoparticles, encoding for conserved internal IV A proteins (nucleoprotein [NP] and/or matrix protein 1 [M1]), induced proliferation of NP-and M1-speci c CD4 + 1 cells as well as NP [147][148][149][150][151][152][153][154][155] -speci c CD8 + T cells in mice. All vaccinated mice survived hetero-subtypic IV A challenge [64]. Evidence suggests that innate immune stimulation leads to a broader adaptive immune response [64].…”
Section: In Uenza Virus (Iv)mentioning
confidence: 99%
“…All vaccinated mice survived hetero-subtypic IV A challenge [64]. Evidence suggests that innate immune stimulation leads to a broader adaptive immune response [64]. A Toll-like receptor 2 (TLR2)-agonist together with a split IV vaccine, but not vaccine alone, protected mice against homologous and heterologous virus challenge.…”
Section: In Uenza Virus (Iv)mentioning
confidence: 99%
“…Vaccination with self-amplifying mRNA (SAM ® ) (GlaxoSmithKline, London, UK) in lipid nanoparticles, encoding for conserved internal IV A proteins (nucleoprotein [NP] and/or matrix protein 1 [M1]), induced proliferation of NP-and M1-specific CD4 + Th1 cells as well as NP147-155-specific CD8 + T cells in mice. All vaccinated mice survived heterosubtypic IV A challenge [64]. Evidence suggests that innate immune stimulation leads to a broader adaptive immune response [64].…”
Section: Influenza Virus (Iv)mentioning
confidence: 99%
“…All vaccinated mice survived heterosubtypic IV A challenge [64]. Evidence suggests that innate immune stimulation leads to a broader adaptive immune response [64]. A Toll-like receptor 2 (TLR2) agonist together with a split IV vaccine, but not vaccine alone, protected mice against homologous and heterologous virus challenge.…”
Section: Influenza Virus (Iv)mentioning
confidence: 99%